Interview tips & traps - Leigh, Richard; Video Education Australasia (Australia : Video Education Australasia, 2000)
This program explores the best way to prepare for the job interview, including research, attitude, knowing the question themes such your likes, insight and skills and practical considerations
Title from title screen
Executive producer, Stephen Skok ; editor & graphics, Richard Leigh ; sound, Joel de Courcy Browne ; camera, Sasha Trikojus...[et al.]
Voive over: Gary Newton
Keywords: Employment interviewing; Career education; Job hunting; Interviewing